PENGARUH PERSAINGAN ANTAR KANTOR AKUNTAN PUBLIK, AUDIT FEE, AUDIT TENURE PADA INDEPENDENSI AUDITOR (STUDI KASUS PADA KANTOR AKUNTAN PUBLIK DI PROVINSI BALI) - Kadek Krisna Devi (Hita Akuntansi dan Keuangan, 2021)
The profession of public accountant is a profession of public trust, so that in carrying out its duties, an auditor must have independence. This study aims to determine the effect of competition among public accounting firms, audit fees and audit tenure on auditor independence at public accounting firms in Bali province. The population in this study are auditors who work at 16 Public Accounting Firms in Bali Province who have been registered at the Indonesian Institute of Public Accountants (IAPI), while those who are used as research objects (samples) are 93 people. Sample using purposive sampling method. Data analysis using many test, such as: validity, reliability, multicollinearity, heteroscedasticity, multiple regression analysis, hypothesis testing and the coefficient of determination. The results showed that the competition variable between Public Accounting Firm and audit tenure had a negative and significant effect on the independence of auditors at the Public Accounting Firm in Bali Province, while the audit fee had a positive and significant effect on the independence of auditors at the Public Accounting Firm in Bali Province.